Imaging Membrane Potential with Voltage-Sensitive Dyes - Vucinic, Dejan; Kosmidis, Efstratios; Falk, Chun X.; Cohen, Lawrence B.; Loew, Leslie M.; Djurisic, Maja; Zecevic, Dejan (Biomedical Optical Imaging, 2009)
An optical measurement of membrane potential using a molecular probe can be beneficial in a variety of circumstances. One advantage is the possibility of simultaneous measurements from many locations. This is especially important in the study of the nervous system and the heart in which many parts of an individual cell, many cells, or many regions are simultaneously active. In addition, optical recording offers the possibility of recording from processes that are too small or fragile for electrode recording. Several different optical properties of membrane-bound dyes are sensitive to membrane potential, including fluorescence, absorption, dichroism, birefringence, FRET, nonlinear second harmonic generation, and resonance Raman absorption. However, because the vast majority of applications have involved fluorescence or absorption, these will be the only subjects of this review. All the optical signals described in this chapter are “fast” signals (Cohen and Salzberg, 1978) that are presumed to arise from membrane-bound dye; they follow changes in membrane potential with time courses that are rapid compared with the rise time of an action potential. Figure 6.1 illustrates the kind of result that is used to define a voltage-sensitive dye. In a model preparation, the giant axon from a squid, these optical signals are fast, following membrane potential with a time constant of less than 10 µsec (Loew et al., 1985) and their size is linearly related to the size of the change in potential (e.g., Gupta et al., 1981). Thus, these dyes provide a direct, fast, and linear measure of the change in membrane potential of the stained membranes.